Policies and best practices in addressing digital equity gaps: a multisite case study of leaders within a community college system - Calfa, Vicki Bowman (My University, 2025)
This qualitative multisite case study examined the policies and best practices adopted by a large, urban community college system to recognize and address digital equity gaps. Guided by Feenberg’s critical theory of technology and Resta and Laferrière’s five dimensions of digital equity, the study explored how leaders operationalized asset-based approaches to support students, particularly those from low-income, first-generation, and underrepresented backgrounds. Data were collected through document analysis and semi-structured interviews with 21 leaders representing executive administration, faculty, student services, and information technology. Coding and thematic analysis revealed six overarching themes: (a) digital equity practices guided by policies, (b) finding and meeting needs, (c) connecting students to resources, (d) technology as a tool to increase access, (e) student focused multidisciplinary decision making, and (f) lessons learned from the COVID 19 global pandemic. Seven promising practices emerged, including a laptop loan program, a PC repair lab, embedded success coaches, mobile success librarians, community-based technology courses, community partnerships for technology access, and a digital equity rubric for course design. Findings indicated that intentional, policy aligned practices, coupled with cross functional collaboration, enhanced students’ access to technology and related support.
Keywords: Asset-based; Community college; Digital equity